Catch Assessment of Marine Fishes in Cabalian Bay, Philippines: Composition, Abundance, Gear, and Catch Rate - Patual Catherine; Sarsale Jackylou; Siega Marilou; Sarsale Anna Marie (Croatian Journal of Fisheries)
Marine fisheries play a crucial role in food security and livelihoods but face challenges from overfishing and environmental changes. This study assessed fish composition, abundance, fishing gear usage, and catch per unit effort (CPUE) at three key landing sites in Cabalian Bay, Philippines. Seventy-three fish species from 31 families were recorded, with the dominance of Carangidae (11%) and Scombridae (10%). Monthly fish catch data reveal fluctuations in fish abundance, with Scombridae consistently recording the highest catches, particularly in August, December, and January. Hook-and-line and gill net were the primary gear used with varying effectiveness across the landing sites. Simple handline (pasol) was the most widely used gear. Tawa recorded the highest CPUE in Pong-oy, while other gear remained consistently low across all months. These findings provide essential baseline data to support fisheries management and small-scale fishers. The study highlighted the need for strengthened marine protected areas and more sustainable fishing strategies to mitigate declining fish stocks and ensure the long-term sustainability of resources.